Health profile of the elderly person accompanied by the family health strategy in a countryside of Ceará - Brazil - José Rogécio de Sousa Almeida; Lorrainy Solano; Marco Aurelio M Freire; Lucidio C Oliveira (Hospital de Clínicas de Itajubá, 2022)
Objective: To evaluate the correlation between functional dependence and emotional state, cognitive function, and ambulation of the elderly people accompanied by a family health team. Methods: A cross-sectional, quantitative, and prospective study was conducted in the city of Quixeré/CE between August 2020 and April 2021. Participated in 229 elderly people registered in the Family Health Strategy teams evaluated using the Lawton scale, MMSE, GDS-15, and Tinneti test. The association of variables was verified using the chi-square or Fisher's exact tests. Odds Ratio (95%CI) were calculated, followed by logistic regression using the Hosmer and Lemeshow test. Results: The sample was primarily composed of women with low education, average age of 70 years, and a high demand for primary health services. Women were more vulnerable to depression, with no difference in falls related to sex. Age was a risk factor for all aspects evaluated. There was a correlation between functional dependence and all aspects analyzed. There was a relationship between the level of functional dependence and education (OR: 2.0; 95%CI: 0.05 - 78.32), living in the rural area (OR: 2.83; 95%CI: 1.6 - 5.1), depression (OR: 5.18; 95%CI: 1.2 - 22.8) and risk of falls (OR: 1.67 CI: 0.8 - 3.5), with the last two factors remaining significant in the logistic regression. Conclusion: Functional dependence to more complex daily activities among the elderly was significant, with an essential relationship with emotional and cognitive aspects and risk of falls.